A JUDICIALIZAÇÃO DOS CONFLITOS ESCOLARES - Goethel, Elisiane Spencer Quevedo [UNESP]; Polido, Caroline [UNESP]; Fonseca, Débora Cristina [UNESP] (Centro de Estudos Educação e Sociedade, 2020)
This article aims to discuss the judicialization of school relations, as well as the punitive and educational aspects of the actions taken by the school. To reach this goal, judicial proceedings, iniciated by the iniciative of the school against elementary students, were analyzed. This paper is a documentary research of qualitative analysis, where the technique of content analysis was applied. The study points out that situations of violence occurring within the school are being directed to the justice system in an attempt to have the conflict removed and resolved out of school.

Este artigo tem como objetivo discutir a judicialização das relações escolares e os aspectos punitivos e educativos das ações tomadas pela escola. Para tanto, foram analisados processos judiciais de alunos do Ensino Fundamental II que tiveram sua origem por iniciativa da escola. Trata-se de uma pesquisa documental de análise qualitativa, na qual foi utilizada a técnica de análise de conteúdo. O estudo aponta que as situações de violência ocorridas no âmbito da escola estão sendo direcionadas para o sistema de justiça na tentativa de que o conflito seja afastado e resolvido fora da escola.
THE JUDICIALIZATION OF SCHOOL CONFLICTS
Keywords: School conflicts; Judicialization; School; Infraction act; Conflitos escolares; Judicialização; Escola; Ato infracional